Effects of thymoquinone and etoposide combination on cell viability and genotoxicity in human cervical cancer hela cells - Celebioglu, Hediye Gamze Nur; Kizilkaya, Merve Becit; Caglayan, Aydan; Dilsiz, Sevtap Aydin (Istanbul Journal of Pharmacy, 2022)
Background and Aims: It is thought that thymoquinone might have a crucial role in preventing DNA damage, regulating DNA repair mechanisms, and inhibiting the formation of a cancer. Studies on the cytotoxic and genotoxic effects of thymoquinone together with etoposide in cervical carcinoma cells (HeLa) are not adequate. The objective of this study is to evaluate the effect of combinations with thymoquinone on etoposide cytotoxicity and genotoxicity in HeLa cells. Methods: Cytotoxicity was evaluated by MTT assay and genotoxicity was determined by Comet assay. Results: The I[C.sub.50] values of thymoquinone were 233.6 [micro]M and 145.5 [micro]M, and the I[C.sub.50] values of etoposide were 167.3 [micro]M and 52.7 [micro]M for 24 and 48 h, respectively. Thymoquinone significantly decreased the approximate I[C.sub.50] value of etoposide in doses of 15.63 [micro]M and above for 24 h and 31.5 [micro]M and above for 48 h in a dose-dependent manner. 0.1-5 [micro]M thymoquinone and 1 [micro]M etoposide alone did not cause DNA damage, but at higher doses increased DNA damage significantly in a dose-dependent manner. Thymoquinone significantly reduced DNA damage induced by 10 [micro]M etoposide at the doses of 0.1-10 [micro]M. Conclusion: Our results show that thymoquinone might increase the cytotoxic and genotoxic effects of etoposide in HeLa cells at high doses and reduce DNA damage at low doses that are not cytotoxic, which suggests that etoposide may increase its anticancer effect at high doses, but comprehensive studies are needed on this subject. This study is a preliminary study and will contribute to the development of new treatment strategies. Keywords: Thymoquinone, etoposide, cytotoxicity, genotoxicity, comet assay, HeLa cells